(untitled) (Journal of the College of Education for Women, 2019)
The early childhood is a dangerous period for the development of childrenin their present and future life . It is important to design programs for the preschoolperiod .These programs are relatd to the childs Personality and its integration .The most effective stories and attractive programs for the child is the objectivestories which can develop his self-canfidence . Therefore the kindergartenshould participate in developing the childs personality and experiencebecause it is the most effective institute in the childs life .The present study aims at finding out the effect of the narrative program inthe kindergartens . This has been done by investigating the truth of a numberof hypotheses to measure the self-confidence , the researcher used aproeedure deigned by the researcher herself who has also designed anarrative program for the children .The research sample consists of fourteen ( ) male and ( ) females .The researcher has deliberately chosen ghernata kindergarten . Theprocedures used are :1- The t- test for two independent consisting of the same number ofchildren .2- Berson confficient equation .3- The t-test equation for two samples the researcher has come up withthe conclusion depending on the results of research the researcher hasput forward recommendations and suggestions .